123k views
10 votes
Which expression is equivalent to -51 - (-60)?

Choose 1 answer:
-60+ (-51)
-51 + 60
60 + 51
51 - 60

User Mjh
by
5.3k points

2 Answers

2 votes

Answer:

Answer: B. -51 + 60 = 9

Explanation:

-51 - (-60)

= -51 - (-60) = -51 + 60

= -51 + 60 = 9

= 9

So, now we answer these

A. -60 +(-51) = -111

B. -51 + 60 = 9

C. 60 + 51 = 111

D. 51 - 60 = -9

Hopes this Helps :D

User Junsu Cho
by
5.8k points
3 votes

Answer:

-51 + 60

Explanation:

negative times negative equal positive

User TheDoc
by
5.4k points